2021
DOI: 10.3390/ijerph18136702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resisted Sprint and Plyometric Training on Lower Limb Functional Performance in Collegiate Male Football Players: A Randomised Control Trial

Abstract: The main objectives of this study were to evaluate the short-term effects of resisted sprint and plyometric training on sprint performance together with lower limb physiological and functional performance in collegiate football players. Ninety collegiate football players participated in this three-arm, parallel group randomized controlled trial study. Participants were randomly divided into a control group and two experimental groups: resisted sprint training (RST) (n = 30), plyometric training (PT) (n = 30), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Maximal Voluntary Isometric Contraction Strength (STN) Test: We used an ISOMOVE dynamometer, software version 0.0.1 (ISO-MANSW-IT; Tecnobody, Dalmine (BG), Italy), to assess the maximum peak torque of quadriceps muscles strength dominant leg before strength training and after 8-weeks of training. The reliability of quadriceps strength measurements of the ISOMOVE dynamometer was previously validated ( Hasan et al, 2021 ). Participants completed the warm-up session and were familiarized with the equipment before data collection.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Maximal Voluntary Isometric Contraction Strength (STN) Test: We used an ISOMOVE dynamometer, software version 0.0.1 (ISO-MANSW-IT; Tecnobody, Dalmine (BG), Italy), to assess the maximum peak torque of quadriceps muscles strength dominant leg before strength training and after 8-weeks of training. The reliability of quadriceps strength measurements of the ISOMOVE dynamometer was previously validated ( Hasan et al, 2021 ). Participants completed the warm-up session and were familiarized with the equipment before data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to stand with their forward legs placed closer to the starting line, and then on verbal command, they started sprinting with a maximal speed over a 50 m distance. All the performances were recorded by a handheld stopwatch (XINJIE, SW8-2008) times (in seconds) ( Hasan et al, 2021 ; Alonazi et al, 2021 ; Zafeiridis et al, 2005 ) when the participant’s foot touched the finishing line. The subsequent two sprint test trials were performed after 5 min recovery period, and the lowest timing of the two scores was considered the pre-test (baseline) scores.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, other sports adopted it as well (10,11) .Research has shown positive outcomes of plyometric training in both athletes and non-athletes. Its advantages include improved muscle strength, joint function, stability, reduced chances of significant knee problems, and improved running economy (12,13) .Similarly, yoga asanas are physical positions or postures mainly focused on enhancing steadiness, comfort, and a joyful spirit (14) . Asanas (static postures) are designed to engage all targeted and supporting muscle groups while maintaining a regular and steady breathing rhythm (15) .…”
Section: Introductionmentioning
confidence: 99%